Memória social em Leite derramado, de Chico Buarque : uma alegoria da formação do Brasil moderno - Canabarro, Tânia Cristina Vargas (2014)
Based on the novel Leite derramado (Spilledmilk), by Chico Buarque de Hollanda, this thesis focuses on the study of brazilian social memory in the formative period of modern Brazil, portrayed in the novel by the narrator Eulálio. In this sense, the hypothesis guiding this study is that the novel can be read as an allegory of Brazil, since the character-narrator gets his, the memory of the country. To confirm this hypothesis, this paper attempts to explore two aspects of memory in Leite derramado (Spilledmilk): one from reading Proust made by Deleuze, the memory of the person acting as a search for truth and the other from Le Goff, memory collective, making room for studies Ecléa Bosi. Ie: at the junction of the two aspects, found in the narrator of the novel, one can work at the individual and collective memory as form and matter to the allegorical construction of brazilian history that would put two simultaneous search of a truth: the personal and social. Thus, by means of Eulálio’s senile memory, the reader can trace an overview of the major brazilian social problems that occurred in the late nineteenth century and early twentieth century, such as: class conflicts, patriarchy, the decay of the traditional oligarchy of the country, the existing prejudices against minority social groups.